BUSINESS MODEL AS A VALUE MANAGEMENT TOOL - Todoruk, Sergy; Kyfyak, Viktoria; Антохов, Андрій (My University, 2021)
Urgency of the research. In the crisis conditions of quarantine, business modelling has become the subject of scientific debate and demand from businesses. Applying conservative approaches to business models has caused significant financial losses and depreciation of business value. Thus, value models that reflect the assessment of various business processes in monetary terms are becoming especially relevant. Therefore, managers understand the synergetic effect of the procedural approach to business processes construction and the component contribution of business processes in achieving the goals of the enterprise. The research purpose is the improving of the scientific principles and development of a methodical approach to improvement of scientific bases and the formation of a business model from a value point of view, which has practical significance for the formation of a vision of business development. Uninvestigated parts of general matters defining. In the conditions of social crisis and fluctuations, many tools of business development and its business modelling have lost their relevance. Businesses need to find the latest approaches to business structuring and development. Research methodology. The basis of the study is a systematic analysis and a comprehensive approach to the formation of methods for building a cost-effective business model of the enterprise. Analysis and synthesis were used to characterize approaches to business modelling and determine their features, and the dialectical method was used to formulate the essence of the category “business model”. Using statistical methods allowed to get trends in the business and its modelling analysed. For a complex representation of the model, a graphical method was used (for visualization of the model) and economic mathematical modelling for the representation of the model, which has practical significance in the trends of digitalization of business processes. Results. The article substantiates that the formation of a value business model is a prerequisite for a radical rethinking of business approaches, creating the potential for its development and a starting point for innovation and change. After analysing different approaches to business modelling and to estimating the value of business on the basis of a systematic approach, a value business model is proposed, which consists of a value rhombus and a square of potential. This model includes all business processes of the enterprise and assesses the potential of business development. The mathematical expression of the components of the model that corresponds to the process approach and cost evaluation and can serve as a tool for forming a software product is proposed. The advantages of applying such a model in practice are substantiated. Practical implications. The business model and clear well-defined mechanisms of its formation are a necessary requisition for business development. Scientists are often inclined to think that a business model is a complex mathematical or econometric expression. However, in practice, it is the graphic visualization of the business structure that is important in terms of forming a deep understanding of business as a system and areas for improving its components. Value/originality. The proposed approach to business modelling can be used in the following areas: evaluation of business efficiency as an individual enterprise, and in comparison as well; assessment of investment attractiveness of the business; assessment of business potential and directions of its development; analysis of the market potential of the enterprise; strategic analysis of business development and determination of its competitive advantage; a basis for the software or systems of the Workflow class development.
Keywords: business model; valuation; development potential; business development; system approach